Performing domestic duties - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen are the family’s breadwinners, but they also do housework, especially when the wife is away or unavailable. In addition to their domestic duties, Koli fisherwomen manage various outdoor activities, such as taking processed fish to local markets or selling them as mobile vendors in residential areas, contributing significantly to the family income.